TWEETING BACK: EXPLORING BLACK FEMINIST HASHTAG COMMUNITIES ON TWITTER AND INSTAGRAM - Peterson-Salahuddin, Chelsea (AoIR Selected Papers of Internet Research, 2021)
The use of social media by Black women and femmes to talk about topics from a Black feminist perspective has been explored within the larger context of studies on Black Twitter and content analysis of circulated Tweets online. However, studies have yet to empirically study Black feminist social media communities' nuanced dynamics by directly speaking to those involved across a range of networked conversations. To fill this gap, this study conducted 21 semi-structured, in-depth interviews with individuals who engaged in eight different black feminist hashtag conversations across Twitter and Instagram to expand our current understanding of how black feminist intellectual production has been developed and broadened through the affordances of digital media. Findings suggest that while black feminist hashtag discussions have allowed Black women to “talk back” to hegemonic mainstream and popular discourses about Black women, these conversations are constantly at stake of appropriation and co-optation, replicating historical erasure of Black women’s intellectual production.